A Pay Scale of Their Own: Gender Differences in Variable Pay - Jason Sockin; Michael Sockin (CESifo GmbH, 2025)
In the United States and other large economies, women receive less variable pay than men, even within the same firms and job titles. We argue this disparity in pay partly reflects labor market sorting. Since women are less-represented in more variable-pay-intensive jobs, even within occupations, women accumulate less variable pay over time. Women apply relatively less often to and early in their careers separate faster from such roles. Compared with their male peers, women perceive variable-paying jobs as offering worse amenities, including culture, work-life balance, and paid family leave. Compensation schemes appear to induce disparities in pay through worker sorting.
Keywords: J16; M52; 330; gender gap; variable pay; job search; amenities